FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN AKUPUNKTUR SEBAGAI PENGOBATAN KOMPLEMENTER-ALTERNATIF DI KLINIK BUMI SEHAT UBUD, GIANYAR - Purnamayanti Ni Kd Dyah (Coping: Community of Publishing in Nursing, 2014)
Complementary-alternative  medicine is one of the most  attractive  health care in  this time  one  of  them  in  Bumi  Sehat  Ubud,  Gianyar  Clinic.  Based  on  this  fact,  it  is  important  to analyze the factors that influence the use of acupuncture in Bumi Sehat Ubud, Gianyar  Clinic. This is  retrospective cross-sectional study with factor analysis method. Total sampling technique used for collecting data through questionnaires on 100 samples. The results showed 2 factors as factors  that  influence  the  use  of  acupuncture  in  Bumi  Sehat  Ubud,  Gianyar  Clinic.  Factor  1 consists of 56.625%  include  service rates, quality of service, physical environment, experience, knowledge, and attitudes. Factor 2 consisted of 30.323%  include  promotion, access points, and motives. The most dominant factor is the factor 1  consisted of  voluntary service rates, service quality,  conducive  physical  environment,  service  quality,  knowledge  and  attitudes  about acupuncture  is  an  important  consideration  for  users  of  health  services.  Thus,  as  an  effort  to improve the segmentation of the service users need management of health care providers  should pay attention in  infrastructure and superstructure of the services provided.